Pelatihan Pembuatan Anggaran Penjualan Melalui Aplikasi Ms Excel Bagi Pengusaha UMKM 2R Craft Batik Di Desa Plered Bantul - sofiati, sofiati; Linawati; Larasati, Anggia Bintang (LP3M Universitas Putra Bangsa, 2024)
The strategic role of MSME business actors in achieving business success is to increase competence in the field of financial management considering that MSME entrepreneurs are still low in financial behavior, especially the difficulty in planning the number of products to be produced which depends on the level of sales. The aim of this community service activity is to grow batik entrepreneurs in financial behavior through training in making sales budgets. The training method used in this activity involves students by means of counseling, discussion and practical demonstrations by applying MS Excel to participants consisting of 1 owner and 3 employees. The results of the training show the high motivation of participants in financial behavior and proven success. Participants apply the creation of a sales budget. The contribution from the results of this activity is for partners to easily determine the number of products to be produced without over-products or product deficits so that they are efficient.